Be kind to yourself, self-harm is not a choice - Rais, Haniza (New Straits Times Press (M) Bhd., 2021)
Today, the 1st of March, is the World Self-injury Awareness Day (SIAD). This is the day we sit down and contemplate how difficult life can be to some people that the only way to cope is to hurt themselves. There have been misconceptions about self-harm or self-injury(SI) that has left quite a stigma in our society.